A comparative study on diagnostic accuracy of reused clotest® and reused pronto dry® in the diagnosis of helicobacter pylori infection in Hospital Universiti Sains Malaysia (HUSM) - Jamaludin, Shahidi (2011)
Background: Various methods in H.pylori detection are available worldwide with different diagnostic accuracy. In theory, substrate that has not been consumed in a negative rapid urease test can be reused. We investigated the diagnostic accuracy between reused CLOtest® and reused Pronto Dry® in Hospital Universiti Sains Malaysia (HUSM), located in the North Eastern of Peninsular Malaysia with a known low prevalence of H.pylori . Methods: A total of 410 adult patients with dyspepsia between March 2008 to June 2010 who underwent upper endoscopy needing rapid urease test on the basis of endoscopic findings were enrolled in this cross-sectional study. The gastric biospsies were tested for new Pronto Dry® , reused Pronto Dry® ,reused CLOtest® and histology. H.pylori infection was determined by either new Pronto Dry® or histology positive for H.pylori .Results: Reused CLOtest® has higher sensitivity, specificity, PPV and NPV (93%,99%,97%,99% respectively) as compared to reused Pronto Dry® (72.6%,98%,93%,94% respectively). There was perfect kappa agreement between reused CLOtest® and new Pronto Dry®; 0.941(95%CI, 0.841-1.037). The overall prevalence of H.pylori among dyspepsia patients who underwent upper endoscopy in HUSM was 17.8%(73/410). Younger age group, Chinese ethnicity, underlying gastritis and peptic ulcer disease, and gastric ulcers and duodenitis on histology were strongly associated with H.pylori infection in multivariate analysis (p-value<0.05). Conclusions: Reused CLOtest® is superior than reused Pronto Dry® on diagnostic accuracy. Reused CLOtest® can be considered to be used as a screening tool in the diagnosis of H.pylori infection in circumstances in which there are environmental and economic considerations to be taken into account.